Synergetic thermodynamic/kinetic separation of C3H8/CH3F on carbon adsorbents for ultrapure fluoromethane electronic gas. Issue 5 (19th January 2023) - Huang, Jiawu; Peng, Junjie; Wei, Xuan; Du, Shengjun; Yang, Cuiting; Xiao, Jing
Abstract: Atomic layer etching (ALE) using the environmentally friendly electronic gas fluoromethane (CH3 F) is guided for fabricating nanoscale electronic components. The adsorptive purification of CH3 F provide a viable direction to remove trace amounts of impurities to produce highly pure CH3 F (>99.9999%) for the ALE process. Herein, to remove trace propane ( 100 ppm) in CH3 F, we report synergetic thermodynamic and kinetic separation of C3 H8 /CH3 F over glucose‐derived carbon molecular sieve CMS‐T, (T as pyrolysis temperature). With pore size slightly larger than the kinetic diameter of C3 H8, CMS‐600 allows both strong confined adsorption of C3 H8 and a higher diffusion rate of C3 H8 over CH3 F, resulting in a remarkable separation factor of 51.1. Breakthrough experiment demonstrates a high dynamic production capacity of 457 L kg −1 of 7 N CH3 F (<100 ppb of C3 H8 ) over CMS‐600 with excellent cycling stability. Adsorption purification over carbon provides a feasible approach for industrial hyperpurification of electronic gas.